A new species of the genus Archaeoheilus Legalov, 2018 (Coleoptera: Curculionidae) from the Paleocene of Menat (France) - Legalov, Andrei A. (Comptes rendus palevol)
A new molytine species, Archaeoheilus gallicus n. sp. from the Paleocene of Menat (France) is de-scribed and illustrated. The new species is similar to A. provectus (Scudder, 1876), A. scudderi Legalov, 2018, A. ovalis Legalov, 2018 from the early-middle Eocene Green River Formation, and A. lacoei (Scudder, 1893) from the late Eocene Florissant Formation. But it differs from them in the narrow elytral interstriae. The new species differs also from A. scudderi in the thicker rostrum, larger body size, and wider tarsomeres 2 and 3; and also from A. provectus, A. ovalis, and A. lacoei in the thinner rostrum; from A. provectus and A. lacoei in the smaller body size, and from A. ovalis in the larger body size and antennal scrobes reaching eyes. The key to species of the genus Archaeoheilus Legalov, 2018 is given. The links between the weevil faunas of America and Europe in the Paleogene are discussed.